2020
DOI: 10.21203/rs.2.21482/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global dissection of the BAHD acyltransferase gene family in soybean: Expression profiling, metabolic functions, and evolution

Abstract: Background: Members of the BAHD acyltransferase (ACT) family play important roles in plant defence against biotic and abiotic stresses. A better understanding of the functions that specific members of this family play in stress defence can lead to better breeding strategies for stress tolerance. Previous genome-wide studies explored other acyltransferase families, but so far not a single study has been published on genome-wide or positive selection analyses of the BAHD genes in Glycine max . Results: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…Malonyltransferase Ss5MaT2, although also associated with acyl modification, is classified in clade III because it does not contain conserved sequences common to clade I. Therefore, attention will also be paid to PgBAHD14,30,46,61,62,73,74 and 88. Based on sequence structure, physicochemical properties, function, and distribution on chromosomes, the identified PgBAHDs showed a high degree of diversity, which is consistent with previous reports on BAHD gene families (Moglia et al, 2016;Zhang et al, 2019;Ahmad et al, 2020;Liu et al, 2020b).…”
Section: Discussionsupporting
confidence: 90%
“…Malonyltransferase Ss5MaT2, although also associated with acyl modification, is classified in clade III because it does not contain conserved sequences common to clade I. Therefore, attention will also be paid to PgBAHD14,30,46,61,62,73,74 and 88. Based on sequence structure, physicochemical properties, function, and distribution on chromosomes, the identified PgBAHDs showed a high degree of diversity, which is consistent with previous reports on BAHD gene families (Moglia et al, 2016;Zhang et al, 2019;Ahmad et al, 2020;Liu et al, 2020b).…”
Section: Discussionsupporting
confidence: 90%
“…The soybean genome encodes 103 BAHD acyltransferases, which can be classified into four clades (I–IV) (Ahmad et al, 2020). We implemented a co‐expression analysis strategy to identify putative GmSSAcT genes in the soyasaponin biosynthetic pathway using 12 functional known soyasaponin genes, including β‐amyrin synthase1 ( GmBAS1 ), three cytochrome P450 genes CYP93E1 , CYP72A61 , CYP72A69 and eight glycosyltransferase genes UGT73F2 , UGT73B4 , UGT73P2 , UGT91H4 , UGT91H9 , UGT73F2 , CSyGT1 , and SSAT1 .…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis suggested that soybean gained SSAcT activity after its separation from other leguminous plants. Clustered with six other ACT genes ( Glyma18G268100 , Glyma18G268200 , Glyma18G268400 , Glyma18G268500 , Glyma18G268600 , and Glyma18G271600 ; all annotated as flavone/isoflavone malonyltransferases) on chromosome 18 in the soybean genome (Ahmad et al, 2020), GmSSAcT1 probably arose from a flavone/isoflavone malonyltransferase gene by gene duplication and neofunctionalization, coupled with a change in expression pattern, given that flavone/isoflavones are widely distributed in leguminous plants (Panchy et al, 2016). The selection pressure imposed by null‐acetyl type‐A soyasaponins on seed germination allowed the fixation of the recently evolved GmSSAcT1 in the soybean population.…”
Section: Discussionmentioning
confidence: 99%